Hospital-Acquired Blood Stream Infection in an Adult Intensive Care Unit - Jeffrey Harte; Germander Soothill; John Glynn David Samuel; Laurence Sharifi; Mary White (Critical Care Research and Practice)
Background. Hospital-acquired blood stream infections are a common and serious complication in critically ill patients. Methods. A retrospective case series was undertaken investigating the incidence and causes of bacteraemia in an adult intensive care unit with a high proportion of postoperative cardiothoracic surgical and oncology patients. Results. 405 eligible patients were admitted to the intensive care unit over the course of nine months. 12 of these patients developed a unit-acquired blood stream infection. The average Acute Physiology And Chronic Health Evaluation II (APACHE II) score of patients who developed bacteraemia was greater than that of those who did not (19.8 versus 16.8, respectively). The risk of developing bacteraemia was associated with intubation and higher rates of invasive procedures. The mortality rate amongst the group of patients that developed bacteraemia was 33%; this is in contrast to the mortality rate in our unit as 27.2%. There was a higher proportion of Gram-negative bacteria isolated on blood cultures (9 out of 13 isolates) than in intensive care units reported in other studies. Conclusion. Critical-care patients are at risk of secondary bloodstream infection. This study highlights the importance of measures to reduce the risk of infection in the intensive-care setting, particularly in patients who have undergone invasive procedures.